Análise do desempenho de dutos enterrados para arrefecimento de uma habitação na zona bioclimática 2 - Camargo, Mariela (2017)
In the face of broad discussions about sustainable development, energy efficiency and bioclimatic architecture, more and more actions are needed to enable energy saving in civil construction. In order to do this, it has invested in studies for natural air conditioning, since this is one of the great demands of electricity of the residential sector. In the midst of new technologies, a widespread method in the 1970s has returned to the scientific milieu: so-called buried ducts or earthtubes, which consist of heat exchangers that use the high thermal inertia of the soil to cool the internal air of buildings. Due to this problem, the present study sought to investigate the passive cooling by pipelines buried in a hypothetical building located in the city of Santa Maria - RS, in the Bioclimatic Zone 02. The analysis was developed in computational scope, through simulations in the EnergyPlus software , through three different situations for the same building: Case-Base A, no buried duct, Case-Base B, no duct and with calculated natural ventilation, and Reference Cases, where several possible buried pipe geometries were combined. For the Reference Cases, different diameters, lengths, depths, number of air renewals and soil cover type were tested, generating a total of 216 arrangements. The results were evaluated from the number of degrees-hours of cooling and the number of hours in comfort, following the concepts of adaptive comfort. From these data, it was possible to draw a comparative diagnosis between the main variables that acted on the results. Among the most relevant aspects, it was observed that the increase in length, depth and number of air renewals per hour. And with the reduction of the diameter and the naked cover of the ground, are properties that contribute to the good operation of the system. Therefore, after the critical evaluation of the results, it was possible to choose a combination of buried duct variables considered indicated due to the high comfort indexes and the low number of degree-hours of cooling. The simulation, whose variables are: diameter of 0.20 m, 50 meters in length, duct ground depth of 3.0 meters, with twenty renovations per hour and with the soil discovered of vegetation; was listed as the most advantageous situation. This arrangement provided for Zone 1, 94.13% thermal comfort and 65 degree-hour cooling; for Zone 2, 94.08% thermal comfort and 62 degree-hour cooling; and for Zone 3, 84.23% thermal comfort and 256 degree-hour cooling. In this way, the use of underground pipelines proved to be efficient in terms of passive cooling, being a bioclimatic strategy that is functional for the climate under consideration and, therefore, can be better explored by construction professionals.